RAGE Differentially Altered in vitro Responses in Vascular Smooth Muscle Cells and Adventitial Fibroblasts in Diabetes-Induced Vascular Calcification - Kennon, Amber M.; Stewart, James A. (Frontiers in Physiology, 2021)
The Advanced Glycation End-Products (AGE)/ Receptor for AGEs (RAGE) signaling pathway exacerbates diabetes-mediated vascular calcification (VC) in vascular smooth muscle cells (VSMCs). Other cell types are involved in VC, such as adventitial fibroblasts (AFBs). We hope to elucidate some of the mechanisms responsible for differential signaling in diabetes-mediated VC with this work. This work utilizes RAGE knockout animals and in vitro calcification to measure calcification and protein responses. Our calcification data revealed that VSMCs calcification was AGE/RAGE dependent, yet AFBs calcification was not an AGE-mediated RAGE response. Protein expression data showed VSMCs lost their phenotype marker, α-smooth muscle actin, and had a higher RAGE expression over non-diabetics. RAGE knockout (RKO) VSMCs did not show changes in phenotype markers. P38 MAPK, a downstream RAGE-associated signaling molecule, had significantly increased activation with calcification in both diabetic and diabetic RKO VSMCs. AFBs showed a loss in myofibroblast marker, α-SMA, due to calcification treatment. RAGE expression decreased in calcified diabetic AFBs, and P38 MAPK activation significantly increased in diabetic and diabetic RKO AFBs. These findings point to potentially an alternate receptor mediating the calcification response in the absence of RAGE. Overall, VSMCs and AFBs respond differently to calcification and the application of AGEs.